Interreligious Friendship after "Nostra Aetate." Four Perspectives - I - Interreligious Friendship after "Nostra Aetate." Edited by James Fredericks and Tracy Tiemeier. New York Palgrave Macmillan, 2015. viii + 229 pages. $29.95. - Enriquez, Karen B. (2016)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS0360966916000487/resource/name/firstPage-S0360966916000487a.jpg
Keywords: Rezension